Evaluation of Mung Bean Supplementation for Anaemic Pregnant Women - Selpia Dina, Riska; Ahmad, Mardiana; Hadju, Veni; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Background: The global prevalence of anaemia among pregnant women is 37%, which means that 4 out of 10 pregnant women experience anaemia during pregnancy, 70% of which is moderate and occurs during the third trimester of pregnancy. Methods: Literature review research method based on national and international scientific journals on the evaluation of supplementary feeding of mung bean biscuits to anaemic pregnant women on delivery outcomes. Publications between 2019-2024 on Pub-Med, Science-Direct, Google Scholar, and Semantic databases using the keywords "anaemia in pregnancy", "mung beans", "vigna radiata", "birth outcome". 140 articles were identified then screened resulting in 87 articles, then selection was made regarding abstracts, full text, open access and type of research, 30 articles were obtained. The final process is to read and select eligible articles based on the criteria obtained 30 relevant articles consisting of 4 international articles and 26 national articles. Result:The results of the literature search explain that anaemia in pregnancy is caused by increased iron requirements in pregnant women needed to support pregnancy, coupled with insufficient iron intake, can interfere with uteroplacental oxygenation, potentially inhibiting fetal growth and development. Providing additional food and a good diet for anaemic pregnant women can increase haemoglobin levels. Mung beans contain iron, vitamin C and zinc, and vitamin A which are necessary for the formation of haemoglobin. Giving mung beans can increase Hb levels Conclusion: Mung beans can significantly increase blood Hb levels because they contain iron, vitamin C and zinc, and vitamin A which have many functions in the body, including the growth and differentiation of progenitor cellserythrocytes, the body's resistance to mobilisation of iron reserves throughout tissues and infections.